Maturation of the Mfa1 Fimbriae in the Oral Pathogen Porphyromonas gingivalis - Jae Y. Lee; Daniel P. Miller; Leng Wu; Carolyn R. Casella; Yoshiaki Hasegawa; Richard J. Lamont (Frontiers in Cellular and Infection Microbiology, 2018)
The Mfa1 fimbriae of the periodontal pathogen Porphyromonas gingivalis are involved in adhesion, including binding to synergistic species in oral biofilms. Mfa1 fimbriae are comprised of 5 proteins: the structural component Mfa1, the anchor Mfa2, and Mfa3-5 which constitute the fimbrial tip complex. Interactions among the Mfa proteins and the polymerization mechanism for Mfa1 are poorly understood. Here we show that Mfa3 can bind to Mfa1, 2, 4, and 5 in vitro, and may function as an adaptor protein interlinking other fimbrial subunits. Polymerization of Mfa1 is independent of Mfa3-5 and requires proteolytic processing mediated by the RgpA/B arginine gingipains of P. gingivalis. Both the N- and C- terminal regions of Mfa1 are necessary for polymerization; however, potential β-strand disrupting amino acid substitutions in these regions do not impair Mfa1 polymerization. In contrast, substitution of hydrophobic amino acids with charged residues in either the N- or C- terminal domains yielded Mfa1 proteins that failed to polymerize. Collectively, these results indicate that Mfa3 serves as an adaptor protein between Mfa1 and other accessory fimbrial proteins. Mfa1 fimbrial polymerization is dependent on hydrophobicity in both the N- and C-terminal regions, indicative of an assembly mechanism involving the terminal regions forming a hydrophobic binding interface between Mfa1 subunits.